A basic helix-loop-helix transcription factor, PhFBH4, regulates flower senescence by modulating ethylene biosynthesis pathway in petunia. (16th December 2015) - Yin, Jing; Chang, Xiaoxiao; Kasuga, Takao; Bui, Mai; Reid, Michael S; Jiang, Cai-Zhong
Abstract: The basic helix-loop-helix (bHLH) transcription factors (TFs) play important roles in regulating multiple biological processes in plants. However, there are few reports about the function of bHLHs in flower senescence. In this study, a bHLH TF, PhFBH4, was found to be dramatically upregulated during flower senescence. Transcription of PhFBH4 is induced by plant hormones and abiotic stress treatments. Silencing of PhFBH4 using virus-induced gene silencing or an antisense approach extended flower longevity, while transgenic petunia flowers with an overexpression construct showed a reduction in flower lifespan. Abundance of transcripts of senescence-related genes ( SAG12, SAG29 ) was significantly changed in petunia PhFBH4 transgenic flowers. Furthermore, silencing or overexpression of PhFBH4 reduced or increased, respectively, transcript abundances of important ethylene biosynthesis-related genes, ACS1 and ACO1, thereby influencing ethylene production. An electrophoretic mobility shift assay showed that the PhFBH4 protein physically interacted with the G-box cis -element in the promoter of ACS1, suggesting that ACS1 was a direct target of the PhFBH4 protein. In addition, ectopic expression of this gene altered plant development including plant height, internode length, and size of leaves and flowers, accompanied by alteration of transcript abundance of the gibberellin biosynthesis-related gene GA2OX3 . Our results indicate that PhFBH4 plays an important role in regulating plant growth and development through modulating the ethylene biosynthesis pathway. Abstract : Ornamental plants: regulatory protein makes flowers fade faster Manipulating the production of a protein controlling gene expression in petunia can increase or decrease the lifespan of its flowers. Proteins that regulate biological processes through the activation or deactivation of genes are known as 'transcription factors.' Cai-Zhong Jiang, at the Agricultural Research Service, United States Department of Agriculture in Davis, California, and colleagues studied the transcription factor PhFBH4 in petunia. They found that levels of PhFBH4 dramatically increase as flowers age, stimulated by plant hormones or environmental stresses. When they used genetic techniques to decrease production of PhFBH4, petunia flowers lasted more than 2 days longer than usual; if PhFBH4 was increased, flowers faded sooner. Jiang's team showed that PhFBH4 interacts with genes involved in ethylene synthesis, suggesting that it mediates flower maturity through the production of ethylene, a key plant hormone.